Nanopartículas de ouro suportadas em óxidos mistos de cério e ferro para a redução de NO por CO - Brackmann, Rodrigo (2016)
Cerium-iron mixed oxides (solid solutions) (Ce1-xFexO2-δ, 0 ≤ x ≤ 0.2) were synthesized by the Pechini method and calcined in a two-step procedure (300 and 500 ºC). The oxides were extensively characterized to evidence the effects of Fe inserption into the CeO2 structure. Iron incorporation changed the CeO2 reducibility, reduced the crystallite size and increased the concentration of oxygen vacancies. Consequently, doping had effect on the performance of the catalysts in the redox reaction between NO and CO. As the Ce0,8Fe0,2O2-δ solid solution showed the most interesting properties, it was choosen for the deposition of gold particles by the colloidal method. The gold nanoparticles affected the reducibility of the solid solution and decreased the NO and CO conversions. NO and CO adsorption tests at room temperature, infrared spectroscopy measurements and temperature programmed desorption analyzes were carried out and allowed the proposition of reaction routes between NO and CO at different temperatures for the synthesized catalysts. It was found that the concentration of oxygen vacancies in the oxide lattice determines the NO and CO conversions and the selectivity to N2.